Of other times: Temporality, memory and trauma in post-genocide Rwanda. Issue 3 (September 2019) - Viebach, Julia
This article explores how survivors' experiences of extreme violence change their relationship with time. It draws on extensive fieldwork undertaken with survivors of the 1994 Genocide against the Tutsi and participatory observation of Rwanda's annual commemoration ceremonies. It focuses on the practice of 'care-taking' that survivors engage in at genocide memorials that display human remains and dead bodies. This article identifies the different temporal practices that survivors use to help remake their worlds after the 1994 Genocide. In doing so, it asks: how do survivors construct time through informal mnemonic practices? How do they experience time during the commemoration? And what mode of temporality is inscribed in the materiality of memorials? The article demonstrates that care-taking and imagination produce a symbolic time-reversal, whereas the materiality of the memorial sites preserves the past in the present. The commemoration constructs different temporal logics, such as time homogenisation and a traumatic cyclicalisation, something I describe through the notion of 'trauma-time'. The article concludes that multiple temporalities are produced and reproduced in various attempts to remake lives after genocide that counter simplistic 'before and after' accounts of time dominant in the transitional justice discourse.